Pemberdayaan Masyarakat Desa Gadingkulon Dau Kabupaten Malang melalui Pelatihan Pembuatan Kefir untuk Meningkatkan Nilai Ekonomis Susu Sapi: Community Empowerment in Gadingkulon Dau Village, Malang Regency through Kefir Making Training to Increase the Economic Value of Cow's Milk - Rif'atul Mahmudah; Diana Chandra Dewi; Siti Maimunah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Gadingkulon Village, Dau District, Malang Regency, is one of the villages producing cow's milk, which is quite productive. To increase the economic value of cow's milk, one way of processing it is to make it into kefir. Kefir is a fermented drink made from cow's milk using kefir seeds, which has the benefit of being a probiotic that is needed to maintain body immunity, especially during a pandemic. Training on making cow's milk kefir for a group of cow's milk farmers in Gadingkulon village can provide another alternative for processing cow's milk to produce a halal probiotic product to increase people's immunity during a pandemic while at the same time increasing the selling value of cow's milk which has the potential to increase the income of cow's milk farmers. This empowerment activity was carried out using the observation and training method with the target of PKK women in Gadingkulon Village. The information results stated that the activity participants needed to become more familiar with the terms and benefits of kefir as a probiotic drink, which helps increase body immunity. The results of the community empowerment showed that the participants could understand and practice how to make cow's milk kefir, pack it aseptically, and form a kefir community in the Gadingkulon village.